ANALISIS PENILAIAN SAHAM PT ADARO ENERGY Tbk. PASCA KEBIJAKAN INSENTIF PAJAK - , Syukrial, S.E., Arvan Carlo Djohansjah, S.E, M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The gool of this research is to estimate the intrinsic value of PT Adaro Energy Tbk. shares related to The GovermandRegional of Repuplics Indonesia No. 81 Year of 2007. The approaches of the research are using discounted cash flows method with free cash flow to firm model, and market approach (relative valuation). The data was consisted of the 2008 to 2010 financial statements of PT Adaro Energy Tbk. The DCF is done in such way: the projected financial statements (balance sheet and income statement), projected free cash flow to firm (FCFF), determination of the discount rate, terminal value, and determining the company's value estimation. The process of market approach (relative valuation) analysis is storted with finding comparable companies in a similar line of business, set the multiplplication or rasios. Those multiplplication used to convert the relevant variable of the book value of PT. Adaro Energy Tbk. into the estimated market value. The multiples are PER (Price Earnings Value), PBV (Price to Book Value), and P/S (Price to Sales Ratio). The result of this research is earned by using the discounted cash flow method. In this research, the reconciliation of intrinsic value estimation or fair value of PT Adaro Energy Tbk. determined by setting such weights between the two approaches.